Literature review: An effective method for identifying science and technology updates - Muji Setiyo; Muhammad Latifur Rochman (Universitas Muhammadiyah Magelang, 2023)
Literature reviews have been proven to help researchers and scholars identify research gaps and identify potential new research paths. This shows an exponential increase in literature review articles from 2000 to the present. Therefore, this article introduces a special issue in MESI (Volume 3, Issue 3, 2023) dedicated to a literature review, highlighting five articles covering topics as diverse as plastic waste in road materials, porous hydroxyapatite for bone grafts, magnesium biocomposites, bio-based cutting fluids for manufacturing, contact mechanics perspective for medical therapy, and the concept, technology, and application of a swirl-type microbubble generator. These articles offer important insights into their respective fields, highlighting advances, challenges, and future research directions.